Vital sites and actions: an integrated framework for prioritizing conservation actions and reporting achievement. Issue 6 (19th January 2015) - Overton, Jacob McC.; Walker, Susan; Price, Robbie; Stephens, R. T. Theo; Henson, Sarah; Earl, Richard; Wright, Elaine; Duncan, Richard
Abstract Aim We describe the Vital Sites and Actions (Vital Sites) model and computational framework for prioritizing conservation actions, describing biodiversity trends and reporting the difference made to biodiversity by conservation management. Location We demonstrate the model in New Zealand using ecological integrity as a national biodiversity goal. Methods Vital Sites implements a model of biodiversity, pressures on biodiversity and the benefits to biodiversity of management. Effects of pressures on biodiversity are used to predict vulnerability and future biodiversity patterns over a given time period (e.g. a decade), and management actions affect future biodiversity patterns by reducing pressures. A generalized expression of significance (the marginal contribution to conservation goals) is combined with vulnerability to estimate the benefits of management (BOM), defined as the marginal contribution to goals achieved by conservation action. Because of their dependence on biodiversity and management context, BOM is estimated relative to a defined biodiversity configuration and management scenario. Results Conservation actions with the highest BOM are those that make the largest gains or avert the most loss to national ecological integrity. The 2009 pest control operations are predicted to decrease BOM from additional operations – even far beyond operational boundaries – because BOM depends on the expected future biodiversity configuration. National ecological integrity was predicted to decline, with the 2009 operations making only a small reduction in this predicted decline. Main conclusions Vital Sites provides important advantages for conservation planning and reporting by: (1) incorporating threats, effects of management and future vulnerabilities into identifying conservation priorities, (2) accounting for fundamental contextual and scaling relationships in conservation reporting, and (3) providing a shared conceptual and computational platform for conservation planning and performance reporting. This demonstrates the feasibility of a shared platform for planning and reporting, providing many advantages for conservation agencies.